1980
DOI: 10.1210/endo-107-1-274
|View full text |Cite
|
Sign up to set email alerts
|

Ovary-Dependent Degeneration in the Hypothalamic Arcuate Nucleus*

Abstract: The effects of estradiol valerate and constant light exposure on the histological appearance of the arcuate nucleus were assessed in female rats. Both of these treatments caused significant increases in the numbers of reactive microglial cells and astrocytic granules in the nucleus. Ovariectomy before either treatment prevented the glial reaction, indicating that the experimental manipulations triggered the secretion of an ovarian product which appears to be selectively toxic to the arcuate nucleus. The fact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
58
1

Year Published

1982
1982
2004
2004

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 141 publications
(61 citation statements)
references
References 20 publications
2
58
1
Order By: Relevance
“…Recently it has also been shown that EV-induced PE results in a selective loss of~-endorphin containing neurons with the arcuate nucleus of the hypothalamus (Desjardins et al, 1993). Brawer et al (1980) have demonstrated that ovariectomy prior to EV treatment or continuous illumination prevented the development of hypothalamic pathology in adult female rats, suggesting that an ovarian product is required for the condition to occur. Conversely, chronic exposure to high-physiological concentrations of unconjugated estradiol in gonadectomized male and female rats results in similar senescence-like pathological changes within the arcuate nucleus (Schipper et al, 1982;Brawer et al, 1983).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently it has also been shown that EV-induced PE results in a selective loss of~-endorphin containing neurons with the arcuate nucleus of the hypothalamus (Desjardins et al, 1993). Brawer et al (1980) have demonstrated that ovariectomy prior to EV treatment or continuous illumination prevented the development of hypothalamic pathology in adult female rats, suggesting that an ovarian product is required for the condition to occur. Conversely, chronic exposure to high-physiological concentrations of unconjugated estradiol in gonadectomized male and female rats results in similar senescence-like pathological changes within the arcuate nucleus (Schipper et al, 1982;Brawer et al, 1983).…”
mentioning
confidence: 99%
“…• (Srebro, 1971) and chronic estrogenization (Brawer et al, 1980;Brawer et al, 1983) induce the accumulation of these astrocytic inclusions. As discussed below, this estrogenic effect on Gomori-positive hypothalamic astrocytes may play a critical role in the development of reproductive failure in rodents .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In rodent hypothalamus, the astrocytic inclusions accumulate with aging (Schipper et al, 1981) and chronic estrogen exposure (Brawer et al, 1980(Brawer et al, , 1983. In the hypothalamic arcuate nucleus, chronic estrogenization induces dendritic damage and synaptic remodeling in close proximity to heavily granulated Gomori astrocytes (Brawer et al, 1978;Naftolin et al, 1988;Olmos et al, 1989).…”
mentioning
confidence: 99%
“…The enhancement of the bfl-1 response by estrogen treatment suggests another potential neuroprotective mechanism for this steroid hormone. Microglia express the ER-β estrogen receptor (48), and microglia in the hypothalamus are activated during the estrous cycle or in response to a single estradiol injection (49). Equally, the failure of an early microglial response in the diabetic brain may contribute to increased infarction.…”
Section: Figurementioning
confidence: 99%